Review of carbon dioxide capture and storage with relevance to the South African power sector - Osman, Khalid; Coquelet, Christophe; Ramjugernath, Deresh (South African Journal of Science, 2014)
Carbon dioxide (CO2) emissions and their association with climate change are currently a major discussion point in government and amongst the public at large in South Africa, especially because of the country’s heavy reliance on fossil fuels for electricity production. Here we review the current situation regarding CO2 emissions in the South African power generation sector, and potential process engineering solutions to reduce these emissions. Estimates of CO2 emissions are presented, with the main sources of emissions identified and benchmarked to other countries. A promising mid-term solution for mitigation of high CO2 emissions, known as CO2 capture and storage, is reviewed. The various aspects of CO2 capture and storage technology and techniques for CO2 capture from pulverised coal power plants are discussed; these techniques include processes such as gas absorption, hydrate formation, cryogenic separation, membrane usage, sorbent usage, enzyme-based systems and metal organic frameworks. The latest power plant designs which optimise CO2 capture are also discussed and include integrated gasification combined cycle, oxy-fuel combustion, integrated gasification steam cycle and chemical looping combustion. Each CO2 capture technique and plant modification is presented in terms of the conceptual idea, the advantages and disadvantages, and the extent of development and applicability in a South African context. Lastly, CO2 transportation, storage, and potential uses are also presented. The main conclusions of this review are that gas absorption using solvents is currently most applicable for CO2 capture and that enhanced coal bed methane recovery could provide the best disposal route for CO2 emissions mitigation in South Africa.